PENCIPTAAN BUSANA CARNIVAL CAKRAPALAH SERTA PELATIHAN KOREOGRAFI DAN MAKEUP KECAMATAN KESAMBEN BLITAR - Syarifah Nur Hajja; M. Arif Jati Purnomo; Aan Sudarwanto (Jurnal Abdimas Bina Bangsa, 2023)
The community service activity entitled Creation of Busana Carnival Cakrapalah Choreography and Makeup Training in Kecamatan Kesamben, Kabupaten Blitar, was completed for 2 (two) days, namely on Saturday and Sunday, 29 and 30 July 2023 at the Kantor Kecamatan Kesamben, Kabupaten Blitar, Jawa Timur. This training activity has resulted in a Busana Carnival with the theme "The Power of Cakapalah". The theme of the Busana "The Power of Cakrapalah" has innovative and creative new ideas, so that the people of the masyarakt desa Kesamben, Kabupaten Blitar. Have new competencies as busana carnival creators. Busana Carnival production training will be carried out in stages: include designing busana, designing headwear, designing accessories for chest necklaces, sleeves and legs. The output targets of this activity are the design results of carnival dress designs from Cakrapalah motifs, products made by design, fantasy makeup training, and choreography